(untitled) (Swiss Medical Weekly, 2016)
QUESTIONS UNDER STUDY: To evaluate pregnancy outcome in pregnant women aged ≥45 years, termed very advanced maternal age (VAMA). METHODS: We retrospectively compared the outcome of pregnancies in VAMA patients with controls aged 30 years at time of delivery. Subgroups of singleton and multiple pregnancies were also analysed. Incidences of maternal and fetal adverse outcomes were measured. Statistical significance was set at p <0.05. Odds ratios (ORs) were adjusted where necessary. RESULTS: One hundred and twenty-seven VAMA pregnancies and 2066 control pregnancies of women aged 30 years were analysed. VAMA pregnancies had a higher rate of maternal complications such as gestational hypertension (3.9% vs 0.6%; OR 6.5), preeclampsia (14.2% vs 3.0%; OR 5.4, adjusted OR 4.4) and gestational diabetes (12.6% vs 3.6%; OR 3.8). Likewise, increased need for blood transfusion (3.2% vs 0.7%; OR 4.8, adjusted OR 4.4) and prolonged hospitalisation >7 days (37.8% vs 15.1%; OR 3.42) was found. Infant complications such as prematurity (44.9% vs 16.2%; OR 4.2) and low birthweight <5th percentile (11.0% vs 5.6%; OR 2.1) were also increased. CONCLUSION: Pregnant women of very advanced maternal age (≥45 years) have significantly increased maternal and fetal risks. Women postponing pregnancy or planning a pregnancy in very advanced age should be informed about these risks, in particular before artificial reproductive technologies are applied or “social freezing”.